2002
DOI: 10.1159/000067177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutritional Stress on the Hypothalamo-Pituitary-Gonadal Axis in the Growing Male Rat

Abstract: Background/Objective: Nutritional dwarfing (ND) consists of a decrease in weight and height gain and delayed onset of puberty. The aim of the present investigation was to study the modifications induced in male rats by the nutritional stress of a mere 20% reduction in food intake which, however, started immediately after weaning. Materials and Methods: At weaning, male Wistar rats were divided into two groups: Control (C) and ND. C rats were fed ad libitum with a balanced rodent diet. ND received 80% of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…These findings may result from diminished leptin serum levels in the present nutritional stress model as it was previously demonstrated [11]. There is considerable evidence that indicates that leptin may increase sympathetic nerve signals to brown adipose tissue, kidneys and adrenal glands, with unequivocal sympathoexcitatory actions in rodents [41,42].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…These findings may result from diminished leptin serum levels in the present nutritional stress model as it was previously demonstrated [11]. There is considerable evidence that indicates that leptin may increase sympathetic nerve signals to brown adipose tissue, kidneys and adrenal glands, with unequivocal sympathoexcitatory actions in rodents [41,42].…”
Section: Discussionsupporting
confidence: 59%
“…In a previous study performed in our laboratory, [11] we observed inhibition of somatotrophic and reproductive axes in this nutritional stress model in post-weaning male rats that could be due, at least in part, to a decrease in serum leptin levels, an adipocyte-derived hormone linked to somatic growth, metabolism and reproduction [12][13][14]. These physiological adaptations could be considered as survival advantages during periods of sub-optimal energy intake, ensuring substrate fluxes to issues that require energy constantly (i.e.…”
Section: Introductionmentioning
confidence: 94%
“…Animal models and epidemiological studies suggest that such energy differences could influence reproductive development. Among male rats, a 20% decrease in dietary energy at weaning inhibited reproductive development and reduced serum testosterone levels (Compagnucci et al 2002). Greater caloric intake has similarly been associated with higher circulating estrogen levels in adolescent girls and adult women (Dorgan et al 2003), but not adolescent boys (Dorgan et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ewes, mice and rats subjected to restricted feeding exhibit reduced fertility. Reduced food intake decreases LH and FSH secretion and causes hypogonadotropic hypogonadism [17,28,153]. The adipose mass of an organism represents an energy storage reservoir.…”
mentioning
confidence: 99%